HISTORIS DAN MEKANISME PEMBENTUKAN PERATURAN DAERAH DI INDONESIA - Ardin Ardin (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
Regional regulations in Indonesia are interesting to study because the development of regional regulations in Indonesia follows the ups and downs of the development of central government policies regarding governance in the regions. In the system of establishing regional regulations as a government regulation that can be used as a source of local revenue is arranged in such a way. The mechanism for the formation of regional regulations in Indonesia in the paradigm of governance that is decentralized should be the instrument for the formation of local regulations should be left entirely to the regional government. Thus, local governments can more freely regulate and manage their own domestic affairs. The implementation of regional government functions will be carried out optimally if the implementation of government affairs is followed by granting authority to grant licenses, especially trading business licenses as one of the sufficient recipient sources to the regions. Providing sufficient revenue sources to regions where the amount is adjusted and harmonized with the division of authority between the government and the regions. Keywords: Historical, mechanism, formation of local regulations in Indonesia